2012
DOI: 10.2169/internalmedicine.51.7204
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Apheresis Therapy for Steroid- and Cyclosporine-Resistant Idiopathic Membranous Nephropathy

Abstract: We herein report three cases of Nephrotic Syndrome (NS) with idiopathic membranous nephropathy (IMN) in which the patients were resistant to steroid (PSL) and cyclosporine (CyA) therapy. All three patients had a high risk of renal failure because of persistently high levels of proteinuria. We performed low-density lipoprotein apheresis (LDL-A) and achieved complete remission in two cases. The third patients developed NS relapse and a deteriorating renal function; however, withdrawal from dialysis therapy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Several reports have evaluated the efficacy of LDL-A for non-FSGS diseases, such as MCNS [ 12 ], membranous nephropathy [ 13 , 14 ], lupus nephritis [ 15 , 16 , 17 ], and diabetic nephropathy [ 18 , 19 , 20 , 21 ], but most are case reports/series with a limited number of subjects. Although the number of subjects with each disease apart from FSGS is small, we examined a total of 16 subjects with non-FSGS registered in the POLARIS cohort and found that LDL-A treatment reduced the UP level in those patients at a comparable rate to that in FSGS cases immediately after treatment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have evaluated the efficacy of LDL-A for non-FSGS diseases, such as MCNS [ 12 ], membranous nephropathy [ 13 , 14 ], lupus nephritis [ 15 , 16 , 17 ], and diabetic nephropathy [ 18 , 19 , 20 , 21 ], but most are case reports/series with a limited number of subjects. Although the number of subjects with each disease apart from FSGS is small, we examined a total of 16 subjects with non-FSGS registered in the POLARIS cohort and found that LDL-A treatment reduced the UP level in those patients at a comparable rate to that in FSGS cases immediately after treatment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have found a beneficial effect of plasma exchange and lipoprotein replacement on steroid resistance, 8,9 the underlying mechanism remains unknown. Shalhoub first hypothesized that certain circulating factors increase the protein permeability of the glomerular filtration barrier and researchers have further postulated that the major ''circulating factors'' responsible for steroid resistance are cytokines derived from dysfunctional T cells.…”
Section: Introductionmentioning
confidence: 99%
“…That study also showed that the favorable outcome rate was 50.0% in non-FSGS patients with diseases such as MCN, MGN, lupus nephritis, or DN, which was comparable to or better than the rate in FSGS patients. Sato also reported that LDL-A therapy showed similar efficacy for patients with idiopathic MGN or FSGS (10). …”
Section: Discussionmentioning
confidence: 93%